ENDOVASCULAR TREATMENT OF CHRONIC VENOUS OCCLUSIVE DISEASE — SPECIFICATIONS OF ENDOPROSTHESES AND COMPARISON OF RESULTS - Daniela Bento; Rui Machado; Daniel Mendes; Rui de Almeida (Angiologia e Cirurgia Vascular, 2019)
Introduction: Chronic occlusive venous disease manifests mainly at the level of the iliofemoral vein, and its treatment has been revolutionized by the emergence of endovascular techniques. Venous system stenting has evolved from the existing treatments of arterial occlusive disease. Some arterial stents were used in the venous system with good results, however, the need to improve the characteristics of these devices led to the development of stents dedicated exclusively to venous pathology. In recent years several dedicated endoprostheses have been approved, however, there are few studies comparing their characteristics and results.